Is uneven-aged silviculture best for maximizing ecosystem functioning, services, biodiversity, and resilience in Walloon forests? - Frédéric André; Arthur Guignabert; Hugues Goosse; François de Coligny; Gauthier Ligot; Benoit Courbaud; Mathieu Fortin; Mathilde Pau; Sylvain Marchi; Mathieu Jonard (Regional Environmental Change, 2026)

Drought resilience of three coniferous species from Belgian arboreta highlights them as promising alternatives for future forests in Western Europe - Morgane Dendoncker; Camille Guisset; Mathieu Jonard; Alexandra Delente; Quentin Ponette; Caroline Vincke (Dendrochronologia, 2025)

Adaptive forest management improves stand-level resilience of temperate forests under multiple stressors - Arthur Guignabert; Mathieu Jonard; Christian Messier; Frédéric André; François de Coligny; Frédérik Doyon; Quentin Ponette (Science of The Total Environment, 2024)

Functional traits drive the difference in soil respiration between Gilbertiodendron dewevrei monodominant forests patches and Scorodophloeus zenkeri mixed forests patches in the Central Congo basin. - Benoît Cassart; Albert Angbonga Basia; Mathieu Jonard; Quentin Ponette (Plant and Soil, 2021)

Soil carbon stocks and exchangeable cations in monospecific and mixed pine forests - Daphne López-Marcos; Carolina Martínez-Ruiz; María-Belén Turrión; Mathieu Jonard; Hugues Titeux; Quentin Ponette; Felipe Bravo (European Journal of Forest Research, 2018)

The response of soil solution chemistry in European forests to decreasing acid deposition - James Johnson; Elisabeth Graf Pannatier; Stefano Carnicelli; Guia Cecchini; Nicholas Clarke; Nathalie Cools; Karin Hansen; Henning Meesenburg; Tiina M. Nieminen; Gunilla Pihl‐Karlsson; Hugues Titeux; Elena Vanguelova; et al. (Global Change Biology, 2018)
Acid deposition arising from sulphur (S) and nitrogen (N) emissions from fossil fuel combustion and agriculture has contributed to the acidification of terrestrial ecosystems in many regions globally. However, in Europe and North America, S deposition has greatly decreased in recent decades due to emissions controls. In this study, we assessed the response of soil solution chemistry in mineral horizons of European forests to these changes. Trends in pH , acid neutralizing capacity ( ANC ), major ions, total aluminium (Al tot ) and dissolved organic carbon were determined for the period 1995–2012. Plots with at least 10 years of observations from the ICP Forests monitoring network were used. Trends were assessed for the upper mineral soil (10–20 cm, 104 plots) and subsoil (40–80 cm, 162 plots). There was a large decrease in the concentration of sulphate ( ) in soil solution; over a 10‐year period (2000–2010), decreased by 52% at 10–20 cm and 40% at 40–80 cm. Nitrate was unchanged at 10–20 cm but decreased at 40–80 cm. The decrease in acid anions was accompanied by a large and significant decrease in the concentration of the nutrient base cations: calcium, magnesium and potassium (Bc = Ca 2+ + Mg 2+ + K + ) and Al tot over the entire dataset. The response of soil solution acidity was nonuniform. At 10–20 cm, ANC increased in acid‐sensitive soils (base saturation ≤10%) indicating a recovery, but ANC decreased in soils with base saturation >10%. At 40–80 cm, ANC remained unchanged in acid‐sensitive soils (base saturation ≤20%, ≤ 4.5) and decreased in better‐buffered soils (base saturation >20%, > 4.5). In addition, the molar ratio of Bc to Al tot either did not change or decreased. The results suggest a long‐time lag between emission abatement and changes in soil solution acidity and underline the importance of long‐term monitoring in evaluating ecosystem response to decreases in deposition.

Soil parent material—A major driver of plant nutrient limitations in terrestrial ecosystems - Laurent Augusto; David L. Achat; Mathieu Jonard; David Vidal; Bruno Ringeval (Global Change Biology, 2017)
Because the capability of terrestrial ecosystems to fix carbon is constrained by nutrient availability, understanding how nutrients limit plant growth is a key contemporary question. However, what drives nutrient limitations at global scale remains to be clarified. Using global data on plant growth, plant nutritive status, and soil fertility, we investigated to which extent soil parent materials explain nutrient limitations. We found that N limitation was not linked to soil parent materials, but was best explained by climate: ecosystems under harsh (i.e., cold and or dry) climates were more N‐limited than ecosystems under more favourable climates. Contrary to N limitation, P limitation was not driven by climate, but by soil parent materials. The influence of soil parent materials was the result of the tight link between actual P pools of soils and physical–chemical properties (acidity, P richness) of soil parent materials. Some other ground‐related factors (i.e., soil weathering stage, landform) had a noticeable influence on P limitation, but their role appeared to be relatively smaller than that of geology. The relative importance of N limitation versus P limitation was explained by a combination of climate and soil parent material: at global scale, N limitation became prominent with increasing climatic constraints, but this global trend was modulated at lower scales by the effect of parent materials on P limitation, particularly under climates favourable to biological activity. As compared with soil parent materials, atmospheric deposition had only a weak influence on the global distribution of actual nutrient limitation. Our work advances our understanding of the distribution of nutrient limitation at global scale. In particular, it stresses the need to take soil parent materials into account when investigating plant growth response to environment changes.

Tree mineral nutrition is deteriorating in Europe - Mathieu Jonard; Alfred Fürst; Arne Verstraeten; Anne Thimonier; Volkmar Timmermann; Nenad Potočić; Peter Waldner; Sue Benham; Karin Hansen; Päivi Merilä; Quentin Ponette; Ana C de la Cruz; et al. (Global Change Biology, 2015)
The response of forest ecosystems to increased atmospheric CO 2 is constrained by nutrient availability. It is thus crucial to account for nutrient limitation when studying the forest response to climate change. The objectives of this study were to describe the nutritional status of the main European tree species, to identify growth‐limiting nutrients and to assess changes in tree nutrition during the past two decades. We analysed the foliar nutrition data collected during 1992–2009 on the intensive forest monitoring plots of the ICP Forests programme. Of the 22 significant temporal trends that were observed in foliar nutrient concentrations, 20 were decreasing and two were increasing. Some of these trends were alarming, among which the foliar P concentration in F. sylvatica , Q. Petraea and P. sylvestris that significantly deteriorated during 1992–2009. In Q. Petraea and P. sylvestris , the decrease in foliar P concentration was more pronounced on plots with low foliar P status, meaning that trees with latent P deficiency could become deficient in the near future. Increased tree productivity, possibly resulting from high N deposition and from the global increase in atmospheric CO 2 , has led to higher nutrient demand by trees. As the soil nutrient supply was not always sufficient to meet the demands of faster growing trees, this could partly explain the deterioration of tree mineral nutrition. The results suggest that when evaluating forest carbon storage capacity and when planning to reduce CO 2 emissions by increasing use of wood biomass for bioenergy, it is crucial that nutrient limitations for forest growth are considered.

Deterioration of N orway spruce vitality despite a sharp decline in acid deposition: a long‐term integrated perspective - Mathieu Jonard; Arnaud Legout; Manuel Nicolas; Etienne Dambrine; Claude Nys; Erwin Ulrich; Raphaele van der Perre; Quentin Ponette (Global Change Biology, 2012)
Since the late 1970s, several long‐term ecological studies were conducted to better understand the biogeochemical functioning of N orway spruce stands in the A rdennes as these nutrient‐poor ecosystems were subject to high levels of acid deposition and exhibited symptoms of tree health decline. Between 1978 and 2009, acid deposition declined sharply, especially sulfur and to a lesser extent nitrogen deposition. The aim of this study was (i) to determine if the N orway spruce stands recovered after the reduction of acid deposition and (ii) to explain why such a recovery occurred or not. Therefore, we collected data from different projects carried out in the A rdennes to characterize the long‐term temporal trends in soil solution chemistry, foliar nutrition, and crown condition. In parallel, a model describing the nutrient cycling in forests (Nu CM ) was calibrated and used to check the consistency of the observed temporal trends and to explain them. The soil solution concentration of most of the elements decreased between 1978 and 2002, which was ascribed to a decrease in atmospheric deposition. For potassium, a decline in the exchangeable pool was also showed based on the simulation carried out with Nu CM . As nitrogen (N) deposition remained at an elevated level, N orway spruce stands were progressively saturated in N and mineral nutrition became more and more unbalanced. Except the foliar N and Al concentration that remained constant and increased respectively, the foliar concentration of all other nutrients decreased between 1993 and 2009, which can be explained by the decrease in ion concentration in solution. These nutritional disorders weakened trees and were probably exacerbated during the 2003 summer drought, after which symptoms of vitality loss progressively appeared. In these N‐saturated ecosystems, the N cycle was disrupted by this health decline, which increased NO 3 − leaching reinforcing soil acidification and risk of aluminum (Al) toxicity.

Thirteen-year monitoring of liming and PK fertilization effects on tree vitality in Norway spruce and European beech stands - Mathieu Jonard; Fédéric André; Pierre Giot; François Weissen; Raphaèle Van der Perre; Quentin Ponette (European Journal of Forest Research, 2010)